Investigation of Rectangular Pocket Machining Simulation Using Design of Experiments (DOE) - Mahmood, Shamsuddin; Azli Nawawi; Wan Mohd Wardi Wan Abdul Rahman (Progress in Engineering Application and Technology, 2022)
Design and finite element method (FEM) is a commonly utilized procedure in large volume manufacture of components. The numerous product designs and materials utilized in manufacturing to generate prototypes and commercial items today highlight the competition and tough situations involved in generating a viable product for marketing. The major purpose of this research is to describe the construction of a model by employing the Design of the experiment (DOE). The model explores the influence of various characteristics on the product design of RPM. This helps in determining the process leading parameters for similar items created from four different materials blanked with a tolerable quality on the same design and machining process. The finite Element Method (FEM) and Design of Experiments (DOE) technique are utilized in order to accomplish the specified model goals. The combination of both strategies is recommended to result in a decrease of the required experimental expense and labor in addition to attaining a greater degree of verification. It can be claimed that the Finite Element Method with Design of Experiments technique gives a good contribution towards the optimization of the material in building and design for the optimum purpose of the process in manufacturing technology. The creator or designer will face challenges in terms of design, material selection, tooling selection, process selection, and prototype creation in order to capitalize on market trends. The study is more concerned with the machining process than with product design and material analysis by using finite elements in Solidworks can have a significant impact or effect on the machining process, particularly when using a milling machine with computer numerical control or by hand. The structure, VonMises, displacement, and strain with different forces and mechanical loading are used to determine the path of material with yield strength. A comprehensive framework for design and finite element analysis with the implementation of Doe will improve the efficiency of the product design and machining process.